Manajemen Penanganan Kebakaran Hutan dan Lahan (Karhutla) Guna Peningkatan Ekonomi Kerakyatan - Kunto Arief Wibowo (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Forest and land fires (forest and land fires) continue every year. Since 2014 until that event continues to occur. Various methods have been carried out, but it still happens. This paper aims to explain another method of handling forest and land fires, which uses a populist economic approach with an emphasis on management aspects in management. The method used is qualitative by conducting field research and the use of related references, including the author's direct experience in handling forest and land fire. The results obtained indicate there must be a harmonized management of handling all parties, all involved, including the involvement of agencies which so far have not been actively involved. Understanding of people's economy is needed, because this is the key to effective implementation.